2013 IEEE Security and Privacy Workshops 2013
DOI: 10.1109/spw.2013.27
|View full text |Cite
|
Sign up to set email alerts
|

The Probabilistic Provenance Graph

Abstract: Previous provenance models have assumed that there is complete certainty in the provenance relationships. But what if this assumption does not hold? In this work, we propose a probabilistic provenance graph (PPG) model to characterize scenarios where provenance relationships are uncertain. We describe two motivating examples. The first example demonstrates the uncertainty associated with the provenance of an email. The second example demonstrates and characterizes the uncertainty associated with the provenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A gerência de incerteza em BDs de proveniência tem sido pouco explorada em pesquisas na literatura. Idika et al [2013] discutem um modelo de proveniência genérico que considera relacionamentos com incerteza envolvida. Entretanto, o modelo apresentado não é instanciado em um BD real e nem aplicado a experimentos científicos.…”
Section: Bancos De Dados Probabilísticos E Trabalhos Relacionadosunclassified
“…A gerência de incerteza em BDs de proveniência tem sido pouco explorada em pesquisas na literatura. Idika et al [2013] discutem um modelo de proveniência genérico que considera relacionamentos com incerteza envolvida. Entretanto, o modelo apresentado não é instanciado em um BD real e nem aplicado a experimentos científicos.…”
Section: Bancos De Dados Probabilísticos E Trabalhos Relacionadosunclassified
“…A process aware approach to worm attacks and contamination have been designed, implemented and evaluated in [4]. The authors identified the important issue that provenance un-awareness leads to problems in quick and accurate identification of worm attack point [4]. Process coloring can be assigned to uniquely identify processes, it is inherited by the child processes and diffused through process actions.…”
Section: Related Workmentioning
confidence: 99%
“…A process aware approach to worm attacks and contamination have been designed, implemented and evaluated in [4]. The authors identified the important issue that provenance un-awareness leads to problems in quick and accurate identification of worm attack point [4].…”
Section: Related Workmentioning
confidence: 99%